PENGAWETAN KAYU KELAPA DENGAN METODE RENDAMAN DINGIN - Barly Barly; Sasa Abdurrochim (Jurnal Penelitian Hasil Hutan, 1986)
A  study   on  the   treatability    of  coconut   trunk   was  carried  out  using  the  cold  soaking   method   with   Formula   7, Wolmanit   CB and Diffusol   CB as preservatives.   The specimens  size  50cm  x  5cm  x  5cm  were soaked  in five  percent  pre- servatives  solution   for  period   of  one,  three,  five  and  seven  days.  The  preservatives   retention   and  penetration  were re- corded.  From  this study   the  following   conclusions   could  be drawnThe  densities   and  treatment    schedule   have  a  significant   bearing  on  the  preservatives  penetration  and  retention.Both  factors  have significant   interaction   effect   on preservatives  retention   and penetration.    This implies  that  the densities should  be taken  into  account  in determining   the effectivity  of a treatment   schedule.